The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0886260517744191
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Coping Strategies in the Shadow of Terrorism

Abstract: The present study focuses on spousal differences in reaction to ongoing exposure to terror and security threats. Sixty-eight married couples with children living in a region exposed to ongoing security threats were evaluated. All participants completed questionnaires on objective exposure (number of incidents) and subjective exposure (sense of fear) to terrorism and security threats, posttraumatic stress disorder (PTSD) symptoms, and their coping strategies with this ongoing exposure. Mothers reported higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(100 reference statements)
2
5
0
Order By: Relevance
“…Finally, although at the time the study was conducted there was no indication that the coronavirus acted differently among men and women, the findings show that women had higher levels of psychological distress compared to men. This is in line with previous findings showing that women appear to be more vulnerable to internalizing symptoms, both in studies on the coronavirus (1) as well as in national studies on psychological distress levels (35,43,44). This tendency is well-documented and has been attributed to physiological differences (45), differences in cognitive appraisal and coping (46), socialization, and social factors (47).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, although at the time the study was conducted there was no indication that the coronavirus acted differently among men and women, the findings show that women had higher levels of psychological distress compared to men. This is in line with previous findings showing that women appear to be more vulnerable to internalizing symptoms, both in studies on the coronavirus (1) as well as in national studies on psychological distress levels (35,43,44). This tendency is well-documented and has been attributed to physiological differences (45), differences in cognitive appraisal and coping (46), socialization, and social factors (47).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in line with previous findings (e.g., Laufer et al, 2019;Qiu et al, 2020;Wang et al, 2020;Shechory Bitton and Cohen-Louck, 2021), women were found to display more fear than men. They also used more coping strategies and had less resilience compared to men.…”
Section: Gendersupporting
confidence: 92%
“…In contrast, high levels of emotion-focused coping are proposed to have positive effects on adaptation in uncontrollable situations (Conway and Terry, 1992). In these cases, it may even be better to use emotion-focused coping, since this strategy may reduce the negative psychological effects of the event without confronting it directly (Zeidner, 2006;Shechory Bitton and Cohen-Louck, 2021).…”
Section: Resilience and Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coping refers to cognitive and behavioral efforts to manage the internal and external demands of the interaction between the individual and the environment [21]. Basically, coping styles can be classified into problemfocused coping (e.g., dealing with stress sources and taking proactive steps to change them) and emotion-focused coping (e.g., regulating one's emotion to reduce stress) [23][24][25]. Additionally, coping styles can also be classified as adaptive/functional and maladaptive/dysfunctional [26].…”
Section: Introductionmentioning
confidence: 99%